Fluorescence studies of protein aggregation leading to amyloid formation: the role of anionic lipid membranes - Ricardo, Joana Catarina Ribeiro (2013)
Tese de mestrado em Bioquímica, apresentada à Universidade de Lisboa, através da Faculdade de Ciências, 2012